PERANCANGAN SET PERHIASAN SEBAGAI ALTERNATIF MEDIA SELF SOOTHING BAGI PENGIDAP ANXIETY DISORDER - Dita Mardiana; Maharani Dian Permanasari (PT. Hasba Edukasi Mandiri, 2026)
Mental health awareness in Indonesia still faces significant challenges, particularly due to social stigma that perceives anxiety disorders as personal weakness. This condition limits access to formal mental health services and encourages individuals, especially urban women, to rely on practical and discreet self-coping strategies. This study aims to design a jewelry set as an alternative self-soothing medium for individuals with anxiety disorder. The research method consists of four design stages, beginning with the empathize phase through literature review, observation of users experiencing anxiety, and consultation with a psychologist, and concluding with the prototype phase to produce a tangible design output. Product effectiveness is discussed theoretically based on design principles and expert consultation.